Design of geometric variables of hold-down and angle bracket connections for lateral resistance enhancement of cross-laminated timber (CLT) walls considering the influence of wood species, load-grain angles, and floor conditions. (February 2023) - Khai Tran, Dang; Jeong, Gi Young
Abstract: Geometric variables of hold-down (HD) and angle bracket (AB) connections were designed to enhance the lateral resistance of cross-laminated timber (CLT) walls by investigating the effects of different wood species, load-grain angle, and floor conditions on the shear behaviors. The deformation of HD connections was 40 to 86% higher, and elastic stiffness and resistance properties were 25 to 36% lower than those of AB connections. HD and AB connections in CLT walls with 31% lower wood density exhibited 12% and 30% lower elastic stiffness and resistance, respectively, but 20% higher ductility ratio. The HD and AB connections in a rigid support showed 33 to 177% higher stiffness, but 19 to 61% lower deformation than those in the case of flexible support. When the shear properties of the AB connections were compared between load-grain angle of 0 0 and 90 0, the connections with a load-grain angle of 0 0 showed lower values ranging 18 to 45%, except for the elastic stiffness and ductility ratio. When shear force was applied to HD and AB connections, in-plane and out-of-plane moments were generated, depending on the geometry of the connectors.